PENGARUH MOTIVASI KERJA, KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR KECAMATAN PRAJEKAN KABUPATEN BONDOWOSO - Jamilah, Latifatul; Praja, Yudha; Pramesthi, Riska Ayu (Relawan Jurnal Indonesia, 2024)
In today’s global competitiveness, workplaces need innovative and productive employees. To achieve high productivity, it is necessary to increase performance. This research aims to analyze and test the influence of work motivation, organizational commitment, and work discipline on employee performance through job satisfaction. The population in this study were civil servants in the Prajekan District. The sampling technique used was saturated sampling. Data analysis and hypothesis testing in this research used the Partial Least Square-Structural Equation Model (PLS-SEM).. The results of direct influence hypothesis testing using the Smart PLS 3.0 application showed that work motivation had a significant effect on job satisfaction, work motivation had no significant effect on employee performance, organizational commitment had a significant effect on job satisfaction, organizational commitment had a significant effect on employee performance, work discipline had a significant effect on Job satisfaction, work discipline had a significant effect on employee performance, job satisfaction had a significant effect on employee performance. The indirect influence hypothesis test results showed that the work motivation variable on employee performance through job satisfaction had a significant positive effect, and organizational commitment on employee performance through job satisfaction had a positive but insignificant effect. Work discipline on employee performance through job satisfaction had a significant positive effect.